The effect of pair work on students’ writing skill for Junior Hight School - Erlik Widiyani Styati; Yuyun Endang Parwati; Vita Vendityaningtyas (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2021)
The purpose of this research is to see how pair work affects students' descriptive text writing skills. A quantitative research design was adopted in this study. It was a quasi-experimental study using a pret-test and post-test control design. The participants in the study were junior high school students in grades VIII F and VIII G in Madiun, East Java, Indonesia. There were 26 students in grades VIII F and 26 students in grades VIII G. There are 52 students in total. Giving the students a writing test was used to collect data. The descriptive writing test was employed as the instrument. The students were categorized into two groups: the control group and the experimental group. The data was analyzed using an independent t-test in SPSS version 16. The result of this research shows that pair work attests significant difference on the means score of the students’ writing skill on descriptive text for junior high school. Based on the score of the test, the significance value of t-test for equality of means is 0,000. It is less than α =0, 05 (0,000 < 0, 05). Then, the null hypothesis (H0) is rejected and alternative hypothesis (H1) is accepted. It means that there is significant difference on the students’ writing means score in descriptive text after using pair work. Based on the findings, it can be stated that adopting pair work to improve students' descriptive text writing skills in junior high school is successful. Furthermore, pair work allows students to interact with their partners about the issue, gather knowledge, and correct their written content collaboratively. As a result, the teacher must be able to maintain control over the class in order for learning activities to perform efficiently. In the future, researchers are encouraged to do a study on pair work, particularly with eighth-grade junior high school students who are taught to a variety of text types.